2011
DOI: 10.1016/j.jmb.2011.10.026
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tropomyosin Domains in Cooperative Activation of the Actin–Myosin Interaction

Abstract: To establish α–tropomyosin (Tm)’s structure-function relationships in cooperative regulation of muscle contraction, thin filaments were reconstituted with a variety of Tm mutants (Δ2Tm, Δ3Tm, Δ6Tm, P2sTm, P3sTm, P2P3sTm, P1P5Tm, wtTm), and force and sliding velocity of the thin filament were studied using an in vitro motility assay. In the case of deletion mutants, Δ indicates which of the quasi-equivalent repeats in Tm was deleted. In the case of period (P) mutants, an Ala cluster was introduced into the indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 63 publications
4
20
0
Order By: Relevance
“…Our results also show that specific residues of Tm are involved in regulation, because mutation of residues in P2-2-EKD and P3-1-EE mutants did not affect motility. The results agree with previous studies reporting that deletion of P3-P6 had an inhibitory effect on actomyosin (18,19) and that P3 was important for the cooperative activation of the actin filament (20,21).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results also show that specific residues of Tm are involved in regulation, because mutation of residues in P2-2-EKD and P3-1-EE mutants did not affect motility. The results agree with previous studies reporting that deletion of P3-P6 had an inhibitory effect on actomyosin (18,19) and that P3 was important for the cooperative activation of the actin filament (20,21).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed that individual periodic repeats of Tm had varying degrees of effect on thin filament regulation, indicating that specific regions of Tm contribute differently to its regulatory function (18)(19)(20)(21). EM and 3D reconstruction of actin-Tm filaments with different Tm isoforms have shown that in the absence of Tn and myosin, Tm occupies the blocked or closed position on the actin filament, depending on the Tm and actin isoform (22).…”
mentioning
confidence: 99%
“…Fujita and his colleagues demonstrated, in skinned fibers, that the isometric tension increased by ∼50 % after reconstitution with Tm and Tn, compared to tension generated by unregulated actin filament and the thick filament (Fujita et al 2002). In vitro motility assay also demonstrated a similar increase in tension and sliding velocity when Tm and Tn were reconstituted (Oguchi et al 2011; Bing et al 2000a; Kawai et al 2006; Gordon et al 1998; VanBuren et al 1999). From a structural point of view, this allosteric effect may happen because Tm binding to the AM complex recruits more hydrophobic residues to the AM interface, leading to an enhanced AM binding (Holmes 1995).…”
Section: Tm's Allosteric Effect On the Am Interactionmentioning
confidence: 66%
“…The cooperativity of the BVC actin, Tm and Tn-reconstituted myocardium (2.71 ± 0.23) was slightly less than that of the native fibers (3.22 ± 0.18), but with no statistical significance ( P >0.1). Other techniques, such as stopped-flow florescence measurements (Heeley et al 2006), light scattering measurements (Ishii and Lehrer 1990), co-sedimentation (binding affinity) assay (Mirza et al 2007), in vitro motility assay (Barua et al 2012; Oguchi et al 2011), the ATP hydrolysis rate assay (Chang and Potter 2005), and transgenic (Tg) animal models (Muthuchamy et al 1999) have offered valuable information on Tm's role in the AM binding and cardiac diseases. Compared to other techniques mentioned above, the thin-filament extraction/reconstitution ensures that Tm is placed in the native protein environment without any secondary effects, such as fibrosis, myocyte disarray, and altered post-translation modifications which are inevitable in transgenic animal models with disease causing mutations.…”
Section: Using Thin-filament Extraction/reconstitution Technique and mentioning
confidence: 99%
“…19 Previous studies have also shown that individual periodic repeats of Tm are quasi-equivalent and contribute in different ways to actin binding and regulatory function. [20][21][22][23][24] Crystal structures of Tm fragments have shown that the coiled coil structure is not uniform along the length of the molecule and there are variations in the interhelical distance and pitch of the coiled coil as well as bends and staggers in the molecule. [25][26][27] A solution structure of the striated muscle Tm overlap complex gave some insight into how the proposed periodic actin binding sites on Tm relate to the actin monomers in the actin filament.…”
Section: Actin Binding and Actomyosin Regulation By Tropomyosinmentioning
confidence: 99%